TINDAK TUTUR SARKASME TERHADAP ISU KENAIKAN GAJI DPR AGUSTUS 2025 PADA KOLOM KOMENTAR TIKTOK - Syahrani Nazilatur Rahmah, Syahrani; Resdianto Permata Raharjo, Resdianto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines sarcastic speech acts in TikTok comment sections related to the issue of the Indonesian House of Representatives (DPR) salary increase in August 2025. This issue triggered widespread public attention and negative responses, particularly in digital spaces, due to perceived social and economic inequality. The purpose of this research is to identify and analyze the forms of locutionary, illocutionary, and perlocutionary speech acts contained in sarcastic utterances expressed by netizens. This study employs a qualitative descriptive method with a pragmatic approach. The data were collected from comments on TikTok accounts @kompas.com and @cijesfel using documentation and note-taking techniques. The data were analyzed through stages of data reduction, classification, and interpretation based on speech act theory. The findings reveal that locutionary acts generally appear as literal statements, while illocutionary acts predominantly function as expressive sarcasm in the form of satire, criticism, and mockery. Meanwhile, perlocutionary acts show that sarcastic comments influence other users, generating responses such as agreement, reinforcement of criticism, and further sarcastic expressions. These findings indicate that sarcasm serves not only as a linguistic style but also as an effective tool for social criticism and opinion formation in digital communication.